Financial Literacy and Preparation for Retirement - Anne Nolan; Karina Doorley (Institute of Labor Economics (IZA), 2019)
The economic and financial landscape facing individuals as they move through their life-cycle is becoming increasing complex. Internationally, declines in the coverage and generosity of public programmes mean that individuals now need to assume responsibility for a greater share of their future retirement saving and health and long-term care costs. Financial literacy, defined as knowledge of fundamental financial concepts and the ability to do simple financial calculations, is a key skill required to ensure adequate financial protection in older age. In this paper, we investigate the extent to which financial literacy is an important determinant of financial protection in the older pre-retirement population in Ireland. Using data from the Irish Longitudinal Study on Ageing (TILDA), we find significantly higher levels of financial literacy among men, those with higher levels of education and cognition, and the self-employed. Financial literacy is in turn associated with higher total household wealth, lower financial stress and higher expected retirement income. We find little evidence that those with higher levels of financial literacy are more likely to have various forms of supplementary pension cover however, which may reflect a limited role for financial literacy over and above other important determinants such as income and education.
Keywords: J32; E21; 330; financial literacy; retirement; Ireland